Le Boogie Woogie: inside an after-hours club - Williams, Terry M. (The cosmopolitan life, 2020)
Preface -- Introduction -- The setting -- The scene -- The characters -- After-hours now -- Conclusion: a culture of refusal -- acknowledgments -- Appendix 1. Methodological appendix -- Appendix 2. Field note samples -- Appendix 3. Where are they now? -- Glossary of slang at Le Boogie Woogie -- Glossary of slang at Murphy's Bar -- Notes -- Bibliography -- Index.